Renal prognostic value of serum monoclonal immunoglobulin in cryoglobulinemic glomerulonephritis - Ma, Lei; Xia, Yuanyuan; Fan, Yun; Zhou, Dan; Yao, Xinchen; Zhong, Yongzhong; Yang, Fan; Xu, Feng; Liang, Shaoshan; Wang, Yujie; Zhu, Xiaodong; Chen, Dacheng; et al. (Frontiers in Immunology, 2025)
AimsTo explore the clinicopathological features and renal outcome in patients with cryoglobulinemic glomerulonephritis (Cryo-GN) without confirmed systemic autoimmune diseases.MethodsSixty-nine patients with Cryo-GN from a single center were recruited in this retrospective study. Their clinical, pathologic, and follow-up data were collected and analyzed. According to whether the serum monoclonal immunoglobulin (MIg) and HBV-DNA/HBV markers or HCV-RNA/anti-HCV antibodies were positive or not, they were classified into four groups: positive serum MIg only (MIg group), positive HBV-DNA/HBV markers or HCV-RNA/anti-HCV antibodies (HBV/HCV) only (HBV/HCV group), positive serum MIg and HBV/HCV (MIg+HBV/HCV group), and all MIg/HBV/HCV negative group.ResultsThe male-to-female ratio was 1.38:1 with a mean age of 50.4 ± 14.7 years in the patient cohort. Hypertension was presented in 59.4% of cases, anemia in 73.9%, renal insufficiency in 60.9%, nephrotic proteinuria in 44.9% and microscopic hematuria in 94.2%. The MIg group had significantly lower eGFR levels, higher cryoglobulin levels, and higher rates of abnormal serum-free light chain ratios than the MIg/HBV/HCV negative group. The most common histological pattern of Cryo-GN was membranoproliferative glomerulonephritis (MPGN), and the MIg group had significantly higher scores of the severity of intracapillary cryo-Plugs than the MIg+HBV/HCV group and the MIg/HBV/HCV negative group. Immunohistochemical staining of 29 patients revealed a significant infiltration of CD68+ cells within the glomeruli. Further multiplex immunohistochemical staining of 4 of these patients showed that the infiltrating cells within the glomeruli in Cryo-GN were predominantly CD68+CD163+ cells. Sixty-seven patients had a median follow-up of 31.7 months, and 23.9% of them progressed to end-stage renal disease (ESRD). The renal survival was inferior for MIg group than HBV/HCV group. Multivariate analysis showed that serum MIg and eGFR were independent prognostic factors.ConclusionRegardless of the presence of HBV/HCV infection, non-systemic autoimmune diseases related Cryo-GN patients with serum MIg had worse renal function and renal survival. Patients with a large number of pseudothrombi in the glomerular capillary lumens tend to have worse renal outcomes. Serum MIg and eGFR were independent risk factors for renal survival in Cryo-GN patients without autoimmune diseases.